Interactive effects of poultry litter compost and chemical fertilizers on macronutrients, oil and protein content in sunflower (Helianthus annuus L.) - Alauddin, Md; Rahman, MK; Ali, AHM Zulfiquar (Dhaka University Journal of Biological Sciences, 2022)
A field experiment was carried out at the research farm of Charfasson Govt. College, Bhola, during rabi season in 2016-2017 to evaluate the effect of poultry litter compost and NPK fertilizers on concentration, uptake, oil and protein content of sunflower cv. BARI-2 (Keroni-2). The experiment was laid out in a completely randomized block design (CRBD) having sixteen treatments with three replications. The unit plot size was 3 m x 2 m. Treatments were T1: Control (- PL and -NPK), T2:1.5 t PL ha-1, T3:3 t PL ha-1, T4: 4.5 t PL ha-1, T5:N40P30K50 kg ha-1, T6:N80P60K100 kg ha-1, T7:N120P90K150 kg ha-1, T8: 1.5 t PL ha-1+N40P30K50 kg ha-1, T9:1.5 t PL ha-1+ N80P60K100 kg ha- 1, T10:1.5 t PL ha-1+ N120P90K150 kg ha-1, T11: 3 t PL ha-1+N40P30K50 kg ha-1, T12: 3 ton PL ha-1+ N80P60K100 kg ha-1, T13:3 t PL ha-1+ N120P90K150 kg ha-1, T14: 4.5 t PL ha-1+N40P30K50 kg ha-1, T15:4.5 t PL ha-1+ N80P60K100 kg ha-1 and T16:4.5 t PL ha-1+ N120P90K150 kg ha-1. Sixty plants were grown in each plot for 90 days. Maximum values of NPKS concentration (%) in different organs of sunflower were 0.65, 0.42, 1.80, 0.17 for stem; 1.02, 0.54, 1.54, 0.18 for root; 4.47, 0.57, 3.14, 0.20 for leaf; 2.60, 0.64, 3.20, 0.32 for petiole and 5.18, 0.86, 1.02, 0.31 for seed due to application of poultry litter and NPK fertilizers. The highest concentrations of NPKS of different organs of sunflower at maturity, were found significantly (P<0.05) higher in combined treatments 5 t PL ha-1 + N120P90K150kg ha-1 and 7.5 t PL ha-1 + N120P90K150kg ha-1, respectively, in most of the cases. However, their uptake pattern also followed the same trend as in concentration and those were found in same treatments in most of the cases. The lowest concentration and uptake were measured almost in control treatment (-PL and -NPK). Content of oil and protein increased variably due to variation in treatments. The highest content of oil in seed (47.7%) was extracted from the treatment 5 t PL ha-1 + N80P60K100kg ha-1 and the lowest value (37.7%) was recorded in the highest dose of NPK fertilizers and poultry litter which was lower than control treatment. Protein content also followed the same pattern as in oil. The highest content of protein (31.8%) was recorded from the treatment 5 t PL ha-1 + N120P90K150kg ha-1 and the lowest values (18.8%) was observed in control treatment. The overall findings of this study indicated that poultry litter compost in combination with chemical fertilizers can be applied to achieve better concentration, uptake of NPKS in different organs and oil and protein content in seeds of sunflower under field conditions at coastal zone. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 359-369, 2022 (June)